Characterizing Virtues in Finance - Sison, Alejo G. (Journal of business ethics, 2019)
In this article, we shall attempt to lay down the parameters within which the practice of the virtues may be enabled in the field of finance. We shall be drawing from the three main sources, Aristotle, Catholic Social Teaching (CST) and MacIntyre, on which virtue ethics is based. The research question is what ought to be done for financial activities to truly contribute to eudaimonia or human flourishing (Aristotle), to the achievement of three distinct kinds of goods as required of virtue, “those internal to practices, those which are the goods of an individual life and those which are the goods of the community” (MacIntyre), and to “[help] man on the path of salvation” in the midst of complex network of relationships in modern societies (CST). These parameters could then be taken as conditions financiers ought to fulfill in order to live the virtues in their work and across different life spheres.